PEMBERDAYAAN PEKERJA MIGRAN INDONESIA MELALUI AGRIBISNIS PERIKANAN BERBASIS KEAMANAN SISTEM DIGITAL DAN MANAJEMEN LOGISTIK - Rahmat Karim; Sahban Nur; Mahrus Sabang; Puput Kusuma Dewi; Nur Aidilah Ma’rufi Amiruddin (Fakultas Teknik, 2026)
Indonesian Migrant Workers (PMI) in Kuala Lumpur face various challenges in improving their economic well-being, entrepreneurial skills, and ability to safely utilize digital technology to support business activities. These conditions necessitate an empowerment program that focuses not only on enhancing production skills but also on strengthening digital system security and logistics management—factors crucial for business sustainability. This community service initiative aims to enhance the knowledge and skills of PMI in developing fishery agribusinesses through the implementation of effective digital system security and logistics management practices. The program employed the Participatory Action Learning (PAL) method, comprising material delivery, interactive discussions, simulations, hands-on practice, and mentoring. Program evaluation involved pre-tests and post-tests administered to 30 participants to measure improvements in understanding fishery agribusiness, digital system security, and logistics management. The results indicate an increase in participant knowledge across all measured indicators. Program effectiveness was demonstrated by a rise in the average participant score from 56.40 in the pre-test to 89.50 in the post-test—an increase of 33.10 points. Furthermore, participants demonstrated improved capabilities in identifying digital security threats, protecting personal data, leveraging digital technology for business support, and understanding efficient strategies for managing and distributing fishery products. The program positively impacted the capacity, self-reliance, and competitiveness of the PMI. Consequently, integrating fishery agribusiness, digital system security, and logistics management offers an effective and sustainable empowerment model for PMI to strengthen their economic resilience in the era of digital transformation.